2020
DOI: 10.1088/1742-6596/1618/2/022033
|View full text |Cite
|
Sign up to set email alerts
|

Toward flow control: An assessment of the curled wake model in the FLORIS framework

Abstract: In this work, a new controls-oriented wake model is modified and compared to an analytical Gaussian wake model, high-fidelity simulation data, and experimental wind tunnel campaign. This model, called the curled wake model, captures a wake phenomenon that occurs behind yawed turbines, modeled as a collection of vortices shed from the rotor plane. Through turbine simulations, these vortices are shown to have a significant impact on the prediction of the wake steering’s performance. Overall, the results support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The constant C is used to take into account all of the extra terms in Equation 11. Testing from Bay et al (2020) has shown that for all of the cases tried in the manuscript, a value of C = 8 has provided good agreement between the model and experiments/simulations. This value is consistent with what is suggested by Bay et al (2019).…”
Section: Turbulence Modelmentioning
confidence: 84%
See 3 more Smart Citations
“…The constant C is used to take into account all of the extra terms in Equation 11. Testing from Bay et al (2020) has shown that for all of the cases tried in the manuscript, a value of C = 8 has provided good agreement between the model and experiments/simulations. This value is consistent with what is suggested by Bay et al (2019).…”
Section: Turbulence Modelmentioning
confidence: 84%
“…The curled wake is known to affect not only a turbine immediately downstream, but also subsequent turbines within a wind plant. This effect is known as secondary steering and it is important to capture it when using wake models to unravel the full potential of wake steering (Fleming et al, 2018a;Bay et al, 2020;King et al, 2020). The curled wake model uses a simplified version of the RANS equations to predict the wake of a wind turbine in yaw (Martínez-Tossas et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The proposed model has shown an acceptable agreement with the results obtained by large eddy simulations (LES) [28], LiDAR measurements [24,29], and wind tunnel [28,30]. It presents a significant improvement with respect to the models commonly used in commercial packages such as WAsP or OpenWind.…”
Section: Wake Effect Modelmentioning
confidence: 51%